2011
DOI: 10.1111/j.1365-2990.2011.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Unmyelinated axons are more vulnerable to degeneration than myelinated axons of the cardiac nerve in Parkinson's disease

Abstract: These findings suggest that in PD unmyelinated axons are more vulnerable to degeneration than myelinated axons of the cardiac nerve, because α-synuclein aggregates accumulate much more abundantly in unmyelinated axons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 37 publications
(52 reference statements)
4
56
0
Order By: Relevance
“…SNc, locus coeruleus, raphe nuclei, pedunculopontine nucleus, DMV and nucleus basalis of Meynert neurons all have unusually long highly branched axons that are unmyelinated or thinly myelinated. 7,65 This feature is particularly well documented for SNc dopaminergic neurons. Single SNc axons terminating in the striatum are highly branched and possess as many as several hundred thousand synaptic release sites.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…SNc, locus coeruleus, raphe nuclei, pedunculopontine nucleus, DMV and nucleus basalis of Meynert neurons all have unusually long highly branched axons that are unmyelinated or thinly myelinated. 7,65 This feature is particularly well documented for SNc dopaminergic neurons. Single SNc axons terminating in the striatum are highly branched and possess as many as several hundred thousand synaptic release sites.…”
Section: Introductionmentioning
confidence: 97%
“…This symptom has been attributed to a sympathetic denervation of the heart or vasculature. [5][6][7][8][9] In some PD and dementia with Lewy bodies patients, Lewy pathology is present in the peripheral vagal nerve and ganglia. 10,11 These axons originate in the DMV.…”
Section: Introductionmentioning
confidence: 99%
“…5 Lewy pathology has been documented in specific cortical layers (i.e., preferentially in deep layers of high-order sensory association areas). 5,6 Some previous imaging studies have demonstrated decreased cortical thickness in PD, 7,8 but reported results have been inconsistent and have not shown robust associations with disease progression in the absence of dementia. These inconsistencies may be attributable to several factors.…”
mentioning
confidence: 98%
“…We hypothesized that reductions in gyrification would follow the spatiotemporal distribution described in studies of Lewy pathology. 5,6 METHODS Longitudinal cohort participants. Patients with PD (n 5 70) and controls (n 5 70) with a Mini-Mental State Examination (MMSE) score $26 were selected from a large cohort study based on matching for baseline age distribution, sex ratio, and number of follow-up visits (table 1).…”
mentioning
confidence: 99%
“…One possible explanation for persistent autonomic neuropathy even after recovery of sensorimotor nerves is its high content rate of unmyelinated fibers. Unmyelinated axons and long or sparsely myelinated axons are more vulnerable to degeneration than thick myelinated axons 10. Therefore, degeneration of autonomic nerves might be more severe than that of sensorimotor nerves in this case.…”
Section: Discussionmentioning
confidence: 80%